Trends in the Prevalence and Postoperative Surgical Complications for Smokers Who Underwent a Total Knee Arthroplasty from 2011 to 2019: An Analysis of 406,553 Patients - Simmons, Hannah L.; Grits, Dan; Orr, Melissa; Murray, Trevor; Klika, Alison K.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2022)
Smoking is a modifiable risk factor for complications following total knee arthroplasty (TKA). It is unclear if the declining prevalence of tobacco use in the U.S. population is reflected in patients undergoing elective TKA. This study aims to investigate (1) the incidence of 30-day complications following TKA in smokers and (2) trends in preoperative smoking status among TKA patients. In this study, patients undergoing primary elective TKA in the United States from 2011 to 2019 were identified in the American College of Surgeons' National Surgical Quality Improvement Program (ACS-NSQIP) database. Our cohort included 406,553 cases, 8.13% of which had smoked cigarettes within 1 year of undergoing TKA. Smokers were propensity score-matched to a group of nonsmokers, with each n = 32,533. The incidences of 30-day complications, readmission, and non-home discharge were compared between groups. The rate of preoperative smoking among elective primary TKA patients remained stagnant from 2011 to 2019. Smokers had higher rates of superficial surgical site infections (SSIs; 1.1 vs. 0.5%, p < 0.001), deep SSI (0.3 vs. 0.2%, p = 0.012), wound disruption (0.4 vs. 0.2%, p < 0.001), pneumonia (0.5 vs. 0.3%, p < 0.001), and 30-day readmission (3.6 vs. 2.7%, p < 0.001) compared with nonsmokers. No significant trends in 30-day complications were noted between 2011 and 2019. This study supports the success of national efforts to reduce the prevalence of smoking and reports a modest effect within the TKA population. However, almost 1 in 10 patients undergoing elective TKA continues to smoke and maintains a higher risk of postoperative complications.
Keywords: smoking; surgical outcomes; total knee arthroplasty